Unlocking potential: Commanders' perspectives on the work efficiency and skillsets of autistic adults in non-combat military roles. - Selanikyo, Efrat; Sagie, Dovrat; Haas, Talia; Erez, Asnat Bar Haim (Work, 2026)
Background: Autism Spectrum Disorders (ASD), present challenges, particularly with respect to employment. The Roim-Rachok Program (RRP) trains individuals with ASD for roles in the Israel Defense Forces (IDF), to enhance these individuals' workforce integration. To date, no studies have investigated the professional work performance of RRP participants from the perspective of their military commanders. Objective: This study evaluated IDF commanders' perceptions of the work performance of RRP soldiers and assessed the support these soldiers need for optimal accomplishment of their job profiles. Methods: A cross-sectional quantitative study of 45 commanders (M = 27.0, SD = 7.5) was conducted. Data was collected using a 12-item Commanders' Questionnaire (TCQ) that assessed the task performance, independence, work quality, and perseverance of the 70 ASD soldiers under their orders. Descriptive and non-parametric analyses were applied to explore the associations between the commanders' background and their perceptions of these soldiers' performance. Results: Varimax rotation yielded four domains: Performance at Work, Work Quality, Independence, and Perseverance. The commanders rated RRP soldiers similarly to non-ASD soldiers, but gave higher ratings for accuracy and task persistence, and lower ratings for work pace. Older and more senior commanders rated the soldiers' perseverance and independence more highly. No significant associations were found for gender or soldiers' length of service. Conclusions: RRP soldiers excel on tasks requiring accuracy, perseverance, and routines, but face challenges with task versatility and learning new tasks. The structured military environment accommodates ASD individuals well and can serve as a foundation for future civilian employment.